Modeling and Simulation of Protective Relay for Short Circuits in AC Micro-grids using Fuzzy Logic - Aminu, Maruf Asumo (Curtin University, 2016)
The duo of high human appetite for electricity in the 21st century and high human population growth rate entail inadequacy of contemporary electric power protective systems for the emerging micro-grid. This thesis presents results of a research which seeks to propose a new model of protective device for short circuits in ac micro-grids. Response of the proposed relay is consistent with a reliable device. Consequently, a protective relay for short circuits in micro-grids is proposed.